Amphisphaeria hongheensis sp. nov. (Amphisphaeriaceae, Amphisphaeriales) from Yunnan Province, China - Liu, Rui-Meng; Wang, Hao-Han; Zhang, Gui-Qing; Dai, Dong-Qin; Elgorban, Abdallah M.; Karunarathna, Samantha C.; Tibpromma, Saowaluck (Phytotaxa, 2024)
Yunnan Province encompasses the highest fungal diversity in China, and novel fungal species are regularly introduced. Several saprobic fungi were collected during surveys of fungi associated with woody plants in Yunnan Province, Southwestern China. The fungi samples were initially identified as Amphisphaeria. Multi-gene phylogenetic analysis based on combined datasets of LSU, ITS, rpb2, and tub2 regions and morphological characteristics confirmed that the samples represent a previously unidentified fungus belonging to Amphisphaeria, which is named A. hongheensis sp. nov. This paper provides a full description, illustrations, and a phylogenetic tree showing the new species' taxonomic placement.